STRUKTUR HISTOLOGIS MEDULLA SPINALIS ULAR PUCUK (Ahaetulla prasina Boie, 1827) DAN ULAR JALI (Ptyas mucosa Linnaeus, 1758) - , ANIS HAJIZAH, Drs. Johanes Sugiyanto, M. S. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Spinal cord is a part of the central nervous system (CNS) which control the reflex activity and the transmission of impulses to and from the brain. Study about the histological structure of the spinal cord of snake with different type of habitats is very few. This study was conducted to determine whether habitats types affected the histological structure of spinal cord of snakes. There were two species with different habitat types used in this study, those were the Oriental Whip Snake (Ahaetulla prasina) and the Oriental Rat Snake (Ptyas mucosa). The snakes were euthanized using cloroform and then preserved in neutral buffered formalin 10%. The vertebra of the Oriental Whip Snakes were decalcified using decalcification solution while the vertebra of the Oriental Rat Snakes were not. The regions of vertebra taken as atlas, axis, anterior precaudal vertebra, the biggest precaudal vertebra, posterior precaudal vertebra, cloacal vertebra, anterior caudal vertebra, and posterior caudal vertebra. Slides of spinal cords from those eight vertebra regions were made using paraffin method (6 Î¼m of thickness), and stained using Hematoxylin-Eosin (HE) and Toluidine Blue (TB). Qualitative data of morphometric, histological structures, and micromorphometric were analyzed descriptively. The results showed that the Oriental Whip Snake and the Oriental Rat Snake had different shape and size of canalis centralis, as well as different proportion of gray matter in each region. The canalis centralis of Oriental Whip Snake was oval in shape and larger in size while the canalis centralis of the Oriental Rat Snake was smaller and more rounded. The proportion of gray matter also larger in Oriental Whip Snake. Oriental Whip Snake was believed to have a better developed spinal cord to support its reflex activity in arboreal habitat. From this study, it could be concluded that Oriental Whip Snake and Oriental Rat Snake had different histological structure of spinal cord in each vertebra regions.